The unicorn in the barn - Ogburn, Jacqueline K. (Houghton Mifflin Harcourt, 2017)
Fifth-grader Eric's life transforms when he encounters a unicorn in the woods around Chinaberry Creek and discovers a special veterinary clinic that cares for "supernatural exotic patients."